Antennal Sensilla of Queen and Worker Giant Honey Bee Apis dorsata and Stingless Bee Trigona laeviceps in Difference of Density and Ultramorphometric Analysis - Desmina Kristiani Hutabarat; Rika Raffiudin; Berry Juliandi (Universitas Labuhanbatu, 2024)
Antennal sensilla receive many stimuli from the environment. Thus, it is crucial to study the structure of antennal sensilla, especially in the eusocial bees, such as the honey bee Apis dorsata and stingless bee Trigona laeviceps; both have females, queens and workers with different tasks in their colonies. We aimed this study to describe the types, density, distribution, and ultramorphometric measurements of antennal sensilla of queens and workers of A. dorsata and T. laeviceps. The antennae of ten workers and one queen of A. dorsata and T. laeviceps were analyses using scanning electron microscopy. This study revealed two new sensilla types, chaetica and ceoloconica of A. dorsata workers. We also describe seven new types of sensilla of T. laeviceps workers and queen: trichodea, placodea, basiconica, campaniformia, ampullacea, chaetica, and coeloconica. The current study found caste differentiation in the densities of antennal sensilla: the density of antennal sensilla in the workers is higher compared to the queen, both in A. dorsata and T. laeviceps. Age polyethism in the worker caste presumably shapes the diversity of sensilla. Further, asymmetry distribution was observed in the anterior and posterior sides of the antenna, with the anterior sensilla having nearly twice the density of sensilla compared to the posterior side, in both species of worker caste. In ultramorphometric studies we found that trichodea in A. dorsata workers is larger than that of T. laeviceps workers, while interestingly, the placodea of the giant honey bee A. dorsata is smaller than that of the smaller T. laeviceps.